National identity and Europe in times of crisis : doing and undoing Europe - Karner, Christian; Kopytowska, Monika Weronika, 1978- (Emerald Publishing, 2017)
The European Union currently finds itself in the midst of its most profound crises since its creation. In the minds and writings of many commentators, politicians and European citizens, these multiple contemporary crises call the very future of the European project into doubt. Against the backdrop of economic and political crises across the continent, this edited collection examines the discursive workings and processes underpinning both the centrifugal and the centripetal political forces currently reshaping Europe and individual nation-states.
Keywords: 2000-2099; Nationalism -- Europe.; Europe -- Politics and government -- 21st century.; Europe.; elektronické knihy; electronic books